AGAMA DAN AKHLAK: SATU ANALISA KELAYAKAN PENGASUH DALAM KES HADANAH - Noor, Zanariah (Jurnal Syariah, 2019)
With the growing number of failed marriages, questions of custody of the children have become increasingly important. According to the Islamic family law, the mother is entitled to the custody of young children in preference to the father and other relatives. However, the mother will lose her right for a number of reasons, namely if she has any defect of character, such as would render her unfit to has the custody. This article will discuss the qualifications necessary for custody in two aspects. Firstly, the custodian must be a Muslim and secondly, she/he is of good conduct from the standpoint of Islamic morality. This two aspects have been used in court by the disputing parties to cast doubt on the qualification of custody of their opponents. Hence, this article will discuss jurists’ opinion from different school of thoughts as well as approaches used by the shariah court in dealing with these issues.